Smoking habits and alcohol use of patients with tuberculosis at Standerton Tuberculosis Specialised Hospital, Mpumalanga, South Africa - Janke Wessels; Corinna M. Walsh; Mariette Nel (AOSIS, 2019)
Background: A high prevalence of smoking and alcohol use has been reported in patients with tuberculosis (TB) by several researchers, even though these lifestyle habits have a negative impact on prognosis and treatment. Aim: To determine the smoking habits and alcohol use of patients with TB and TB/human immunodeficiency virus (HIV) co-infection, and how it is associated with gender, level of education and body mass index (BMI). Setting: The study was conducted at Standerton TB Specialised Hospital, Mpumalanga. Methods: A cross-sectional approach was applied. A structured interview was conducted by the researcher with each of the 100 hospitalised patients to obtain information about smoking habits, alcohol use and level of education. Weight and height were measured using standard techniques. Results: Almost six out of 10 participants (58%) indicated that they were former (44%) or current (14%) smokers. Nearly half (49%) reported that they used alcohol, with 25% drinking alcohol more than three times per week. Significantly more women than men were non-smokers (60.0% vs. 30.0%) and more men drank alcohol three times or more per week than women (36.7% vs. 7.5%). Participants who indicated that they were either former or current smokers had significantly lower levels of education than participants who were non-smokers (95% confidence interval [CI] [−26.7%; −2.6%] and [−39.9%; −1.0%] respectively). Conclusion: A high percentage of patients with TB and TB/HIV co-infection previously or currently smoked and used alcohol. Smoking and alcohol use are likely to have a negative impact on nutritional status and may further affect the prognosis of patients with TB.